2019
DOI: 10.1016/j.sjbs.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification and sequencing of Date-SRY Gene: A novel tool for sex determination of date palm (Phoenix dactylifera L.)

Abstract: Dioecism has always been an issue in many plant species with its numerous disadvantages, especially in woody trees such as date palms. As one of the most important crops in the Middle Eastern countries, researchers are having problems identifying of sex of the plant in its early stages of development. Hence, proper population stands in the male: female ratio for maintenance is almost impossible in the field for better production. In this study, sex determination of date palm (Phoenix dactilyfera L.) were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 58 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…Although Sudan is not within the belt where jojoba is grown naturally, the successful establishment and production of seeds from the crop that grown at different parts in Sudan, especially at Arkwakeet, indicates that the country could have a real potential investment possibilities for production of seeds and oil if the problem associated with identification of male and female plants at the early stage of development is solved. DNA markers have been extensively used in sex determination of dioecious plant such as Phoenix dactylifera [20], Carica papaya [21] and Simmondsia chinensis [14,16,17,18]. In the present study, the RAPD primer OPG5 1400 ) was in variance to the result of [14] to amplify a unique male-specific fragment as shown in Figure1.…”
Section: Preparation Of Bulked Dna Samplementioning
confidence: 79%
“…Although Sudan is not within the belt where jojoba is grown naturally, the successful establishment and production of seeds from the crop that grown at different parts in Sudan, especially at Arkwakeet, indicates that the country could have a real potential investment possibilities for production of seeds and oil if the problem associated with identification of male and female plants at the early stage of development is solved. DNA markers have been extensively used in sex determination of dioecious plant such as Phoenix dactylifera [20], Carica papaya [21] and Simmondsia chinensis [14,16,17,18]. In the present study, the RAPD primer OPG5 1400 ) was in variance to the result of [14] to amplify a unique male-specific fragment as shown in Figure1.…”
Section: Preparation Of Bulked Dna Samplementioning
confidence: 79%
“…This problem has recently been solved by the availability of date palm genomes (Al-Dous et al, 2011), verification of sex determination loci (Cherif et al, 2013) and construction of genetic map (Mathew et al, 2014), validating that date palm has a homomorphic XY chromosome system. This sex chromosome is currently being used to develop precise sex-specific markers for specific varieties and populations of date palm (Mohei et al, 2017; Ali et al, 2018; Intha & Chaiprasart, 2018). Thus, it is potential that genome sequencing of Asian Palmyra palm could help us verify the sex determination region and, perhaps, the sex determination system in Asian Palmyra palm.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of information regarding the genetics of date palm. Several cytological studies have showed heteromorphic chromosome pair in male plants and different appearance of sexual chromosomes DOI: 10.2478/arls-2019-0005 ARLS, 3(1), 2019, [17][18][19][20][21][22] in date palm [7]. Although the results were useful to distinguish between male and female date palm, and recently DNA fingerprinting techniques have been considered as reliable and quick methods for sex determination in date palm plants [8].…”
mentioning
confidence: 99%
“…RAPD . Date palm genome has a region linked to gender which had been identified a few years ago, in this region there are sex determination sequences [21]. Date palm is heterogametic sex (XY) in male over and above there is significant polymorphism in the alleles of male and female which can be helpful in the process of sex determination [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation